O Brasil nas guerras dos outros: o interesse nacional em meio a ressignificações sistêmicas (1914 - 1919 & 1930 - 1945) - Mros, Günther Richter (2019)
The involvement of Brazil in the two World Wars is the theme of this thesis. The continuous perception of the two events as a single historical time has as an initial chronological landmark the years from 1914 to 1919 (beginning of World War I and negotiations of the Versailles Peace Treaty respectively). The continuous perception goes through the period began in 1930, in Getulio Vargas administration (understood as a historiographic break and the beginning of a new state profile in Brazil), until ending in the year 1945, when the Conferences that established the order after World War II took place. The central issue we propose deals with the direct and indirect motivational elements of Brazilian involvement in the two World Wars. Among these elements, it is possible to propose a decisional boundary between the internal dimension and the external dimension of national politics in 1917 and 1942, dates marked by the declarations of war of Brazil. We analyze three variables related to Brazil's involvement in the two World Wars: As independent variables, the attacks on merchant ships and passenger ships by German submarines and the blockades imposed on trade. As dependent variables, the symbolic enemy built around the figure of the Germans in the two events, the geopolitical relation with the neighbors and the approach with the United States. Finally, as intervening variables, the Wars in the strict sense and the resignification of the international system in the broadest sense. The thesis we defend is that the Brazilian governments saw in the two World Wars the opportunity to insert the country in the systemic transformations and to claim for Brazil a more relevant role. We understand that this process has taken place continuously, with the action equally divided between the external dimension (the perception of the re-significances of the international system) and the internal dimension (through the reification of the national identity). The Capes' Sandwich Program Abroad funded this thesis.